Changes in the Mentality of Rural Inhabitants at the Turn of the 19th/20th Centuries (Recorded in Public Discourses and Ethno-Historical Sources) - Józefów-Czerwińska, Bożena (Studia Warmińskie, 2022)
The phenomenon of the cultural and social transformation of the rural population taking place at the end of the 19th and beginning of the 20th century has been the theme of many academic studies. Nonetheless, certain contexts are still important for analysis, especially when we turn to ethno-historical sources. The systemic policy of Russification, a consequence of the fall of the January Uprising, continued during this period. Various groups of the Polish elite protested against this oppressive policy, at the same time recognizing the need to strengthen ties in peasant families with Polish national identity. Progressive elites, social activists, and others took up the mission of spreading education, recognizing the need to struggle against illiteracy, still prevalent among the rural population. Particular hopes were attached to educating young generations of peasants in the language, culture, and history of Poland. Undoubtedly, many people contributed to this process, but alongside them, the press also played in this issues an important role.